(untitled) (Baltic Journal of Sport and Health Sciences, 2015)
Background. There is evidence of greater whole body cooling induced unpredictable task switching and memory deterioration in men than in women; however, it is not known how whole body cooling affects attention stability. This study aimed at identifying if there are any gender-specific differences in the effect of cold water immersion- induced stress on attention stability. Methods. Thirteen men and thirteen women were exposed to acute cold stress by immersion in 14°C water until rectal temperature reached 35.5°C or for a maximum of 170 min. Thermoregulatory response (i.e. changes of body temperature and metabolic heat production) and attention stability response (i.e. Schulte table (less cognitively demanding task) and Schulte-Gorbov table (more cognitively demanding task)) were monitored. Results. During cold stress, body temperature variables decreased (p < .05) and did not differ between genders. Metabolic heat production was greater (p < .05) in men than in women. Body cooling significantly increased (p < .05) the duration of Schulte table performance for both genders, whereas an increase (p < .05) of the duration of Schulte-Gorbov table performance was observed only in men. Conclusion. This is the first study to find the evidence supporting the idea of gender-specific and task-dependent attention stability response after whole body cooling. Whole body cooling induced stress had similar influence on simple attention stability task in men and women, whereas more complex task was adversely affected only in men. This greater men’s decrement of complex task performance can be associated with their greater catecholamines- induced metabolic heat production. Keywords: men, women, cognitive performance, metabolic heat production, shivering.